A chimeric il-15/il-15rα molecule expressed on nfκb-activated dendritic cells supports their capability to activate natural killer cells† - Bosch, Naomi C.; Martin, Lena Marie; Voskens, Caroline; Berking, Carola; Seliger, Barbara; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (International Journal of Molecular Sciences, 2021)
Natural killer (NK) cells, members of the innate immune system, play an important role in the rejection of HLA class I negative tumor cells. Hence, a therapeutic vaccine, which can activate NK cells in addition to cells of the adaptive immune system might induce a more comprehensive cellular response, which could lead to increased tumor elimination. Dendritic cells (DCs) are capable of activating and expanding NK cells, especially when the NFκB pathway is activated in the DCs thereby leading to the secretion of the cytokine IL-12. Another prominent NK cell activator is IL-15, which can be bound by the IL-15 receptor alpha-chain (IL-15Rα) to be transpresented to the NK cells. However, monocyte-derived DCs do neither secrete IL-15, nor express the IL-15Rα. Hence, we designed a chimeric protein consisting of IL-15 and the IL-15Rα. Upon mRNA electroporation, the fusion protein was detectable on the surface of the DCs, and increased the potential of NFκB-activated, IL-12-producing DC to activate NK cells in an autologous cell culture system with ex vivo-generated cells from healthy donors. These data show that a chimeric IL-15/IL-15Rα molecule can be expressed by monocyte-derived DCs, is trafficked to the cell surface, and is functional regarding the activation of NK cells. These data represent an initial proof-of-concept for an additional possibility of further improving cellular DC-based immunotherapies of cancer.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Adoptive cellular immunotherapy; Dendritic cell; IL-15; Natural killer cell; NF-κB